A Multiple-Feedback UWB LNA with Low Noise and Improved Linearity. Issue 4 (4th July 2018) - Zhang, Xin; Wang, Chunhua; Zhao, Lv
ABSTRACT: A 3.1–10.6 GHz CMOS low-noise improved-linearity amplifier (LNA) for ultra-wideband (UWB) applications is presented in this paper. This UWB LNA is designed with multiple-feedback networks and noise/distortion cancellation technique. For better bandwidth extension and less chip-size occupation, a transformer is combined with a shunt feedback resistor to construct the novel multiple-feedback networks. Simultaneously, a modified noise/distortion cancellation technique is adopted in the input stage, to reduce the noise figure (NF) and nonlinear distortion. Simulation results illustrate that this proposed LNA achieves a maximum gain of 14.2 dB with 7.2 mW power dissipation under 1.2 V supply voltage, while having an IIP3 of 4.2 dBm and a minimal NF of 2.5 dB. The chip size is only 0.72 mm × 0.72 mm including the testing pads (core area is 0.57 mm × 0.57 mm).